A preservação dos vínculos familiares: um estudo em abrigos - Volic, Catarina (2006)
The objective of the research on which the present study is based was knowing and analyzing how the family links between families and their children are preserved while they are sheltered in social entities, under protection measure set down by the Child and Adolescent s Statute and applied by judicial authority. Three of seven searched shelters integrate the Casas de Acolhimento Program of the Obra Social Dom Bosco de Itaquera , a social entity linked to the Salesian order of the catholic religion, located in the east region of São Paulo city. The research data were obtained through participant observation and individual interviews. A scheme previously elaborated was used to orientate and to best forward the interviewees' testimonies. The interviewees were: the entity director, the searched shelters coordinators and one family of each shelter, chosen by the professional of the entity, taking as criterion the time of permanence in the shelter - above two years. It was also interviewed, from the Judiciary, a social worker of the Childhood and Youth Jurisdiction of the Regional Forum of Itaquera, under which authority is the searched entity. The analysis of the testimonies began with an attentive reading in order to establish the analytical categories. Afterwards, it was made the survey of the context units related to each category. The data taken from the interviewees' testimonies were organized considering each category. The analysis related them one to another, maintaining the individuality of each one. This analysis had as a starting point a theoretical reflection about the category and its meaning concerned to the studied issue. Afterwards, it was presented the way it was expressed by the interviewees, whose testimonies were mentioned in the integral text to favor the understanding. Then, we expressed the analytical reflections that the testimonies raised. The reflection on the professional practice accumulated by the researcher concerning the studied theme has also contributed to accomplish the present analysis